Analysis of heat and mass transfer characteristics in vertical plate channels with falling film evaporation under uniform heat flux/uniform wall temperature boundary conditions. (May 2017) - Wan, Yangda; Ren, Chengqin; Xing, Li; Yang, Yang
Highlights: A method is used to calculate average Nusselt and Sherwood numbers in vertical plate channels. Cases of uniform heat flux/uniform wall temperature boundary conditions are considered. The effects of the various dimensionless factors on the heat and mass transfer processes are studied. Abstract: The objective of the present study is to investigate the combined heat and mass transfer characteristics in vertical plate channels with falling film evaporation. The liquid film falls along the plates which are externally submitted to uniform heat flux (UHF) or uniform wall temperature (UWT). A method based on combining a one-dimensional (1-D) model and a two-dimensional computational fluid dynamics (2-D CFD) model is used to calculate the average Nusselt and Sherwood numbers. The obtained average Nusselt and Sherwood numbers allow the 1-D model to retrieve the 2-D model results accurately. This improved accuracy will help to promote the control technologies based on an electronic control unit (ECU) for the processes in similar falling film evaporation devices involved. Major dimensionless factors identified are liquid water inlet Reynolds number, moist air inlet Reynolds number, ratio of channel length to half channel width, moist air inlet dimensionless temperature (defined as ( T g, i - T wg, i ) / ( T l, i - T wg, i ) ) and wall heating conditions. Cases of laminar flow are considered. The influences of these dimensionless factors on the average Nusselt and Sherwood numbers are analyzed in detail. Correlations are also proposed for the prediction of heat and mass coefficients.